MEASUREMENT OF WATER DIFFUSION COEFFICIENT FOR UPE/PVC BLEND REINFORCED WITH E-GLASS FIBERS - Majeed, Kawakib; Hasan, Jinan (Iraqi Journal of Science, 2024)
The objective of this work was to study the influence of weight percentageratios of (Unsaturated Polyester/Poly vinyl chloride) blends and E-glassfibre content on the diffusion coefficients of the blends from therelationship between water weight gain Mt and diffusivity for waterimmersed samples. Unreinforced and reinforced ( by one or two layers ofchopped E-glass fibers) samples were prepared by hand lay up methodwith the ratios (95%UPE+5%PVC, 90%UPE+10%PVC and%85UPE+15%PVC), the prepared samples were immersed for 60 days inwater to get the absorption curves. The results of laboratory examinationsshow the absorption curves of water gain Mt against the square root of theimmersion timet are gradual increase until saturation then deviate lowerdue to weight loss of the immersed samples. The diffusion coefficientsvalues have been calculated from the plotted curves, the calculated valuesreveal diffusion coefficients values increased with the increasing of PVCweight percentage and fibre content.